3D finite element analysis of porous Ti-based alloy prostheses. Issue 14 (25th October 2016) - Mircheski, Ile; Gradišar, Marko
Abstract: In this paper, novel designs of porous acetabular cups are created and tested with 3D finite element analysis (FEA). The aim is to develop a porous acetabular cup with low effective radial stiffness of the structure, which will be near to the architectural and mechanical behavior of the natural bone. For the realization of this research, a 3D-scanner technology was used for obtaining a 3D-CAD model of the pelvis bone, a 3D-CAD software for creating a porous acetabular cup, and a 3D-FEA software for virtual testing of a novel design of the porous acetabular cup. The results obtained from this research reveal that a porous acetabular cup from Ti-based alloys with 60 ± 5% porosity has the mechanical behavior and effective radial stiffness (Young's modulus in radial direction) that meet and exceed the required properties of the natural bone. The virtual testing with 3D-FEA of a novel design with porous structure during the very early stage of the design and the development of orthopedic implants, enables obtaining a new or improved biomedical implant for a relatively short time and reduced price.